2016
DOI: 10.1038/bmt.2016.136
|View full text |Cite
|
Sign up to set email alerts
|

Melphalan 200 mg/m2 in patients with renal impairment is associated with increased short-term toxicity but improved response and longer treatment-free survival

Abstract: Data on the effectiveness and toxicity of high-dose melphalan in patients with renal impairment (RI) are lacking. We evaluated the impact of RI on outcomes of patients with multiple myeloma treated with melphalan 200 mg/m 2 (Mel200) and autologous stem cell transplantation. Similar baseline characteristics were seen among 46 patients with creatinine clearance (CrCl) o 60 mL/min (median 50 mL/min, range 20-59) and 103 patients with CrCl ⩾ 60 mL/min (median 83 mL/min, range 60-128). Patients with CrCl o60 mL/min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
28
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 23 publications
3
28
1
Order By: Relevance
“…Moreover, quality of life is lower following progression in patients who thrice weekly have to undergo dialysis and do not always agree to more intensive treatment. It may even be that prolonged progression may also result from higher concentrations of melphalan in DD patients when patients overcome toxicity just after auto‐PBSCT. The next reason for the observation of delayed progression in DD compared to NRF patients could be the inadequacy of criteria for recognising symptomatic progression in DD patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, quality of life is lower following progression in patients who thrice weekly have to undergo dialysis and do not always agree to more intensive treatment. It may even be that prolonged progression may also result from higher concentrations of melphalan in DD patients when patients overcome toxicity just after auto‐PBSCT. The next reason for the observation of delayed progression in DD compared to NRF patients could be the inadequacy of criteria for recognising symptomatic progression in DD patients.…”
Section: Discussionmentioning
confidence: 99%
“…1,4,7,11,19,22 On the other hand, due to increased concentrations of melphalan and its antimyeloma effect, when patients overcome toxicity, one could expect a positive effect on the quality of response and prolongation of time to progression and death. 24,31,32 The positive effects in DD patients may result also from the correct qualification process by itself, because they are not dialysis-dependent multiple myeloma patients are treated with auto-PBSCT, but they are dialysis-dependent patients in whom due to generally good organ function (apart from renal failure) a low number of comorbidities, good performance status (in opposition to not eligible DD patients) and acceptablecompliance, the decision to undergo auto-PBSCT was made. These favourable factors, despite renal failure, are known to positively influence early outcomes following auto-PBSCT and likely increase the probability of PFS.…”
Section: Discussionmentioning
confidence: 99%
“…Major experience has been in the nontransplant setting with improved outcome in those with reversal of renal function. Some studies have also reported on the impact of RI on outcome in the transplant setting with variable results [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]; a few of these have included patients with severe RI or those on hemodialysis [20,21]. While most of these studies are from West, there are only case reports or small series from other parts of the world with little information on the use of eGFR MDRD.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] Melphalan is a DNA-alkylating drug that is highly protein bound, in particular to proteins in red cell membranes, and undergoes~40% renal elimination. 9,[11][12][13][14][15][19][20][21] Low creatinine clearance and haemoglobin, are mediators of melphalan PK, and are in turn strong clinical predictors of improved survival and increased toxicity. [15][16][17] Additionally, PK studies have demonstrated that higher melphalan exposure (above the median of 12.84 mg h/L) is associated with improved survival.…”
mentioning
confidence: 99%